2019
DOI: 10.1186/s13058-019-1135-y
|View full text |Cite
|
Sign up to set email alerts
|

Regular use of aspirin and other non-steroidal anti-inflammatory drugs and breast cancer risk for women at familial or genetic risk: a cohort study

Abstract: Background The use of aspirin and other non-steroidal anti-inflammatory drugs (NSAIDs) has been associated with reduced breast cancer risk, but it is not known if this association extends to women at familial or genetic risk. We examined the association between regular NSAID use and breast cancer risk using a large cohort of women selected for breast cancer family history, including 1054 BRCA1 or BRCA2 mutation carriers. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 53 publications
1
30
0
Order By: Relevance
“…[ 16 , 17 , 35 – 43 ] As only a few studies reported subgroup results, we used data in duplicate studies if studies with the largest number of cancer cases didn’t report those to allow studies to be as inclusive as possible. [ 16 , 35 , 37 , 38 , 42 ] At last, 38 studies met the predetermined criteria for inclusion, with 22 cohort studies [ 3 , 4 , 6 , 10 15 , 44 56 ] and 16 case–control studies. [ 5 , 8 , 57 70 ] Among the 1,926,742 participants of this meta-analysis, there were 97,099 incident breast cancers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 16 , 17 , 35 – 43 ] As only a few studies reported subgroup results, we used data in duplicate studies if studies with the largest number of cancer cases didn’t report those to allow studies to be as inclusive as possible. [ 16 , 35 , 37 , 38 , 42 ] At last, 38 studies met the predetermined criteria for inclusion, with 22 cohort studies [ 3 , 4 , 6 , 10 15 , 44 56 ] and 16 case–control studies. [ 5 , 8 , 57 70 ] Among the 1,926,742 participants of this meta-analysis, there were 97,099 incident breast cancers.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous epidemiologic studies have investigated the relationships between use of aspirin and risk of breast cancer. Some studies have suggested a modest reduction in breast cancer risk in relation to use of aspirin, [ 3 5 ] but a randomized clinical trial of long term use of aspirin and some of recent studies did not support a protective role. [ 6 8 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there has not been strong evidence of GXE, at least for the established breast cancer risk factors that have been tested in large consortia studies [7]. However, most risk models still do not include other risk factors like physical activity and aspirin which are consistent risk factors across the spectrum of absolute risk [8,9].…”
Section: Model Extensions and Updates With New Risk Factorsmentioning
confidence: 99%
“…The estimate of new cancer cases reached 18.1 million worldwide in 2018 [1], with a constantly growing trend that needs to be contrasted by efficacious (chemo) preventive strategies able to counteract the dreadful global burden of this disease [2]. Several preclinical, epidemiological and clinical studies proposed nonsteroidal anti-inflammatory drugs (NSAIDs) as one of the most promising class of compounds for the prevention of different cancer types, including mammary tumors [3], even if their use in long-term treatment is limited by side effects due to cyclooxygenase (COX) inhibition.…”
Section: Nicotinamide In the Prevention Of Breast Cancer Recurrences?mentioning
confidence: 99%